Update on Infection with Varicella-Zoster Virus in Children: A Narrative Review - Uwe Wollina; Anca E. Chiriac; Anca Chiriac (Indian Journal of Paediatric Dermatology)
Varicella-zoster virus (VZV) belongs to the family Herpesviridae. Primary infection with VZV is very high contagious with airborne transmission. VZV can be lifelong latent in cranial nerve and dorsal root ganglia. If it reactivates from infected neurons, it causes herpes zoster (HZ). We review the peculiarities in clinical manifestation, course and management in infants, children and adolescents. VZV infections during pregnancy bear a risk for mother and child. Systemic complications of varicella are very rare during childhood, but of extreme severity. Childhood HZ is rare with an incidence of 0.45 per 1000 children in the age <14 years. In contrast to adults, post herpetic neuralgia is uncommon. Risk factors include diabetes, obesity, HIV infection, severe atopic dermatitis, and uncontrolled asthma. Primary prevention of VZV is done by vaccination. Treatment includes acyclovir and immunoglobulins. HZ vaccination is available for adults only.